A new molecular design platform for high-performance polymers from versatile bio-based tyramine: a case study of tyramine-derived phthalonitrile resin. Issue 3 (14th December 2020) - Chen, Menghao; He, Xian; Guo, Yuhang; Hu, Jianghuai; Liang, Bo; Zeng, Ke; Yang, Gang
Abstract : Tyramine was first introduced into high-performance polymers as a promising monomer platform; the derived phthalonitrile resin exhibits excellent thermal stability and a high T g value. Abstract : A molecular design platform based on tyramine, a widely existing bio-amine with flexible structural modifiability, has been employed to synthesis a novel phthalonitrile matrix resin and curing agent in this work. The structures of the products were verified via nuclear magnetic resonance ( 1 H-NMR, 13 C-NMR), Fourier-transform infrared spectroscopy (FTIR), and elemental analysis (EA) studies. The rheology and DSC data showed that the tyramine-based resin presented a lower melting point and a wider processing temperature window compared with its petroleum-based counterpart. The cured resin exhibited excellent thermal and thermo-oxidative stability, according to thermal gravimetric analysis (TGA) data, and a high glass-transition temperature (480 °C), based on the dynamic mechanical analysis (DMA) curve. The curing chemistry was studied via ex situ FTIR, in situ FTIR, solid-state nuclear magnetic resonance, and molecular simulation studies. The results showed that the methine moiety of the curing agent may initiate –CN polymerization at lower pre-curing temperatures, and the methylene group of tyramine may act as an active site for secondary crosslinking reactions at higher post-curing temperatures.